(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Internet of Things (IoT) must safeguard user privacy and combat risks including eavesdropping, jammer, spoofing, and denial of service. The IoT connects a range of objects to networks to deliver sophisticated and intelligent services (DoS). Examining learning algorithm, unsupervised learning, and reinforced learning-based IoT security measures, we look at the threat model for IoT systems (RL). This paper focuses on ML-based IoT authentication, security systems, safe offloading, and malware detection methods to safeguard data privacy. IoT makes it simpler to link the physical world to computer networks, but IoT systems will eventually need to include privacy and security capabilities for uses like building management and environmental monitoring. IoT systems, which include RFIDs, wireless sensors, and cloud computing, must address security challenges such malware, espionage, distributed denial-of-service (DDoS) attacks, spoofing attacks, intrusions, and distributed denial-of-service (DDoS) assaults. We also talk about the difficulties in implementing these ML-based security methods in real IoT devices